Low-Grade Adenosquamous Carcinoma of the Breast: A Single-Center Retrospective Study and a Systematic Literature Review - Tamminen, Anselm; Boström, Pia (MDPI, 2025)
(1) Low-grade adenosquamous carcinoma (LGASC) is a rare subtype of metaplastic breast carcinoma (MpBC), accounting for fewer than 0.05% of breast cancer cases. Unlike the typically aggressive nature of MpBCs, LGASC is an indolent tumor with an excellent prognosis. Due to its rarity, LGASC is frequently misdiagnosed, particularly in core needle biopsies. Currently, there are no clear treatment guidelines for LGASC. (2) Methods: This study presents a single-center retrospective analysis and a systematic literature review of LGASC. (3) Results: Three LGASC cases were diagnosed among 6462 breast cancer patients in our center, demonstrating its rarity. LGASC has overlapping features with benign sclerosing lesions and is often initially misdiagnosed. LGASC is often overtreated, as its indolent nature is not recognized. It very rarely presents axillary or distant metastases, and in contemporary data, local recurrences are rare, questioning the need for adjuvant therapy. (4) Conclusions: LGASC is a very rare form of breast cancer with an excellent prognosis despite being MpBC and usually a triple-negative breast cancer. It is often overtreated as its unique nature is not recognized.